Livelihood vulnerabilities and diversification of fishing households in Ghana. Issue 7 (3rd October 2019) - Amevenku, Francis K. Y.; Kuwornu, John K. M.; Seini, Alhassan W.; Osei-Asare, Yaw B.; Anim-Somuah, Henry
ABSTRACT: This article reports on a study that employed the livelihood vulnerability approach and Simpson's diversification index to examine the vulnerability and diversification of fishing households in Ghana, using primary data from 715 households. It found significant differences between the vulnerability indexes of the combined areas below the Akosombo dam and the area upstream of the dam. A majority of the households have diversified their activities. Therefore, policy interventions to make fishing households less vulnerable should focus on households upstream of the Akosombo dam. Policy interventions that enhance the diversification of the fishing households to enable them reduce their income risks are important.